Masjid selected mosques and musollas in Malaysia - Azim A. Aziz (ATSA Architects Sdn. Bhd., 2016)
The initial idea to produce this monograph, Masjid: Selected Mosques and Musollas in Malaysia, was to produce a simple monograph of about 50 mosques; from the earliest mosque found in Malaysia, the Kampung Laut Mosque to the latest Mosque, the Raja Haji Fisabilillah Mosque in Cyberjaya. The proposed number of mosques to be featured grew to about 80 mosques due to the inclusion of other notable mosques. There was a suggestion to further increase the number to 99 following the 99 names used to describe Allah. Ultimately, that too was scrapped after the compilers discovered that there were some other notable historical mosques that should be featured, particularly since the materials provided were ready and almost completed. Hence, the title 'Masjid - selected mosques and musollas in Malaysia'. The underlying message or the purpose of the monograph is to record the evolvement of mosque architecture in Malaysia from the oldest surviving mosque to recently built mosques and their history. It also gives a purview of future mosque designs in Malaysia. However, as seen in the past, mosque architecture of the future tends to be a regional occurrence rather than country by country. In recent years, a movement towards mosque architecture has somehow transformed to include many other elements to quality the mosque to become a more sustainable building, which is in line with the aim to produce zero carbon or carbon neutral buildings. Finally, it is the publisher's hope that future additions, or volumes will be produced to continue to record many other notable past and future mosques for easier reference. It is also their hope that this book will contribute or will impart knowledge on mosque architecture to many who are or will be interested to know more about the architecture of the mosque and its future design direction.